2019
DOI: 10.1186/s12909-019-1752-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repeated full immersion simulation training in ureterorenoscopy on mental workload of novice operators

Abstract: Background Difficult surgical procedures may result in a higher mental workload, leading to increased fatigue and subsequent errors. This study was aimed to investigate the effect of repeated simulation training in ureterorenoscopy in a high-fidelity setting on the performance and mental workload of novice operators. Methods Medical students voluntarily participated in the present simulation study. After a didactic and video-based lecture, they underwent simulation trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…NASA‐TLX is a subjective assessment tool of workload based on six weighted subscales: mental demand, physical demand, temporal demand, performance, effort and frustration level, and has been widely utilized in a variety of fields, including medicine 21–23 . Our group also reported that under repeated simulation training in ureteroscopy in a mock operating theater, participants showed a continuous decrease in the mental workload, whereas improvements in the technical skills reached a plateau over the six sessions 24 . In the present study, although significant variability in NASA‐TLX scores existed within each group, the scores were higher in the novice group (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…NASA‐TLX is a subjective assessment tool of workload based on six weighted subscales: mental demand, physical demand, temporal demand, performance, effort and frustration level, and has been widely utilized in a variety of fields, including medicine 21–23 . Our group also reported that under repeated simulation training in ureteroscopy in a mock operating theater, participants showed a continuous decrease in the mental workload, whereas improvements in the technical skills reached a plateau over the six sessions 24 . In the present study, although significant variability in NASA‐TLX scores existed within each group, the scores were higher in the novice group (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Since we did not confirm that every student mastered BP reading, the session we provided in 2019 was not a typical training. However, several recent studies in medical education have reported the advantageous aspects of repeated SBE trainings[ 16–18 ]. Increased cardiopulmonary resuscitation (CPR) training repetition on a simulator with the concomitant improvement of quality in CPR performance was associated with a positive effect on the rescuer’s belief in cardiopulmonary resuscitation, according to a previous study[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that repeated training on the Virtual Haptic Back (VHB) contributed to substantial retention of palpatory skills[ 18 ]. In addition, Abe et al demonstrated the effectiveness of repeated simulation training in ureterorenoscopy to reduce anxiety and improve confidence in medical students[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, across other medical domains, simulation-based training is often associated with improvements in mental workload and situation awareness. 15 , 38 , 39 Thus, we acknowledge that our simulation-based training was ineffective in producing large changes and that perhaps more training time or different training methods with a more diverse set of simulated scenarios are needed to affect RTT perceptions of mental workload and situation awareness during routing QA and treatment delivery tasks.…”
Section: Discussionmentioning
confidence: 99%